Elderly nutritional status effection salivary anticandidal capacity against Candida albicans - Ria Puspitawati; Nurtami Soedarsono; Elisabeth A Putri; Anissha D Putri; Boy M Bachtiar (Universitas Airlangga, 2011)
Background: Elderly often suffer malnutrition and oral candidiasis. Candida albicans (C. albicans) which is the most prominent cause of oral candidiasis, is one of commensal oral micro-flora. Nutritional status affect the characteristic of saliva. Saliva is the regulator in the development of C. albicans from comensal into pathogen. Purpose: The purpose of this study was to determining the correlation between elderly nutritional status with salivary total protein and its activity in inhibiting C. albicans growth and biofilm formation. Methods: Using mini nutritional assessment 30 elderly were classified into normal and malnutrition groups. Total protein of unstimulated saliva was measured using Bradford protein assay. The colony forming unit (CFU) of C. albicans was counted on 72 hours on SDA cultures without (control) or with 2 hour saliva exposure. Biofilm formation was analyzed from the optical density of 10-5 C. albicans suspension without saliva exposure (control) or with exposure of 10.000 μg/ml saliva and incubated in 37° C for 2 days. The suspension was put into 96 well plates, stained with crystal-violet dye, and analyzed using microplate reader. Differences between groups were analyzed using independent t-test or Kruskall-Wallis. Correlation between variables was analyzed using Spearman test. Results: Salivary total protein of normal elderly (1.113.5 ± 1.1143.3) was higher than those of malnutrition (613.6 ± 253.6) but not statistically significant (p > 0.05). The CFU of C. albicans exposed to saliva of normal samples (2.060 cfu/ml) was significantly lower than control (24.100 cfu/ml) and those exposed to malnutrition saliva (5.513.3 cfu/ml). C. albicans biofilm formation is highest in controls (0.177), lower in those exposed to malnourished saliva (0.151) and lowest in those exposed to saliva of good nourished elderly (0.133). Conclusion: Although does not cause significant decrease of salivary total protein, malnutrition in elderly results in lower capacity of saliva in inhibiting the growth and declining the virulence of C. albicans. <span style="font-family: TribuneItalic; font-size: 9pt; color: #231f20; font-style: normal;